Effectiveness of an Integrated Physics E-Book with Virtual Laboratory on Students’ Multiple Representation Skills and Conceptual Understanding - Masrifah, Masrifah; Amiroh, Dewi; Taib, Suryani (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
This research aims to determine the effectiveness of a physics e-book integrated with a virtual laboratory in improving students' multi-representation skills and conceptual understanding. The study applied a nonequivalent control-group design involving 27 second-semester physics education students. The experimental class (11 students) used a multi-representation e-book integrated with a virtual laboratory, while the control class (16 students) used only the multi-representation e-book. Pretest and posttest data were analyzed using normalized gain (N-gain) and Mann-Whitney tests. Results show that the experimental class achieved an N-gain of 0.23 for multi-representation (low category) and 0.48 for conceptual understanding (medium category). The control class achieved 0.19 (low) and 0.39 (medium), respectively. Statistical analysis revealed no significant differences between groups, likely due to the small sample size and the limited use of the virtual laboratory during lessons. Nevertheless, the integrated e-book showed higher average gains than the e-book alone. These findings suggest that integrating virtual laboratory components in e-books can enhance learning outcomes, though implementation factors must be optimized.